2015
DOI: 10.1002/path.4571
|View full text |Cite
|
Sign up to set email alerts
|

Defective erythropoiesis in a mouse model of reduced Fbxo7 expression due to decreased p27 expression

Abstract: During the final stages of erythropoiesis, lineage-restricted progenitors mature over three to five cell divisions, culminating with withdrawal from the cell cycle and the loss of most organelles, including mitochondria and nuclei. Recent genome-wide association studies in human populations have associated several SNPs near or within FBXO7 with erythrocyte phenotypes. Fbxo7 encodes a multi-functional F-box protein known to bind p27 and participate in selective mitophagy. One SNP causes an amino acid substituti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 33 publications
4
44
0
Order By: Relevance
“…This is because cell cycle arrest and differentiation are tightly linked, and it is interesting to note that prevention of one can lead to defects in the other. For example, during erythropoiesis in mice lacking Fbxo7 or overexpressing cyclin E, erythroblasts undergo more cell divisions yet fewer mature cells are produced, causing anaemia and other dysplastic phenotypes (63,64). Fbxo7, by virtue of its stabilisation of p27, can also slow B cell proliferation, and B cells lacking Fbxo7 have a faster cell cycle and show a concomitant reversal in differentiation markers, suggesting a linked mechanism whereby slowing the cell cycle aids differentiation (34).…”
Section: Sustaining Proliferation By Blocking Differentiationmentioning
confidence: 96%
“…This is because cell cycle arrest and differentiation are tightly linked, and it is interesting to note that prevention of one can lead to defects in the other. For example, during erythropoiesis in mice lacking Fbxo7 or overexpressing cyclin E, erythroblasts undergo more cell divisions yet fewer mature cells are produced, causing anaemia and other dysplastic phenotypes (63,64). Fbxo7, by virtue of its stabilisation of p27, can also slow B cell proliferation, and B cells lacking Fbxo7 have a faster cell cycle and show a concomitant reversal in differentiation markers, suggesting a linked mechanism whereby slowing the cell cycle aids differentiation (34).…”
Section: Sustaining Proliferation By Blocking Differentiationmentioning
confidence: 96%
“…To determine functional roles in vivo , we created Fbxo7 null mice, first by crossing Fbxo7 LacZ mice with ActB:FLPe animals , to generate a ‘floxed’ ( Fbxo7 fl ) allele, with LoxP sites flanking either side of exon 4 (Figure A), and subsequent breeding to Zp3 Cre mice , for germline excision ( Fbxo7 − ). Fbxo7 −/+ offspring were backcrossed with WT C57/BL6J mice and bred to homozygosity.…”
Section: Resultsmentioning
confidence: 99%
“…To generate a mouse in which Fbxo7 was lost specifically in dopaminergic neurons, Fbxo7 fl mice were bred with Dat Cre ROSA26 ‐stop‐ YFP animals, which express Cre from the dopamine transporter ( Dat ) promoter . Since our previous studies detected no phenotypes in mice heterozygous for Fbxo7 , we analysed Dat Cre Fbxo7 −/fl animals, which were systemically heterozygous for Fbxo7 expression, in addition to the loss of Fbxo7 expression in dopaminergic cells. Dat +/+ Fbxo7 −/+ and Dat Cre Fbxo7 −/+ mice were used as controls.…”
Section: Resultsmentioning
confidence: 99%
“…In the course of our investigations into the physiological functions of mammalian Fbxo7, we generated mice that are either heterozygous or homozygous for an allele of Fbxo7 containing a LacZ insertion between exons 3 and 4 of Fbxo7 Randle et al, 2015). This insertion severely disrupts expression of all Fbxo7 isoforms but does not completely abolish it (Randle et al, 2015), and thus the phenotype(s) of the hetero-and homozygous animals can respectively be ascribed to moderate or severe under-expression of Fbxo7. In maintaining the colony of LacZ-transgenic animals, we observed that homozygous Fbxo7 LacZ/LacZ males never sired any offspring, while heterozygous males and all genotypes of female were able to produce litters.…”
Section: Resultsmentioning
confidence: 99%
“…interactions (Kuiken et al, 2012), and in cell cycle regulation via Cdk6 activation and p27 stabilisation Randle et al, 2015;Meziane et al, 2011;Laman, 2006).…”
Section: Introductionmentioning
confidence: 99%